In plain sight: hidden Stanislavski: part 2. Issue 2 (3rd July 2022) - Hetzler, Eric
ABSTRACT: A quick search of acting texts on Amazon UK returns 8000 results. This is a staggering number of books about acting. Certainly, there are duplications, and a quick scroll shows that not all of them are how-to books. But even if these amounted to 90% of the total, that's still 800 acting texts. Many of them will be by teachers espousing their own special technique that they have developed over years of performance experience and teaching. This presents some questions: just how "original" are these techniques? How many of them merely re-name the ideas of Konstantin Stanislavski without crediting him? How many even know that their ideas originated from him? As we consider the legacy of Stanislavski in the public mind and his contributions, it is worth exploring where he hides. In this second part, the author will continue the examination of these issues and ideas asking the question: is it possible that Stanislavski's ubiquity is such that he has become hidden and that people are no longer aware of what is his?